2021
DOI: 10.1186/s40792-021-01265-w
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metastasis of cecum cancer with MSI-high and BRAFV600E mutation: a case report

Abstract: Background Cutaneous metastases of colorectal cancer (CRC) are rare, occurring in 0.7% to 5% of cancer patients. Furthermore, the molecular subtypes of cutaneous metastasis of CRC are unclear. Here, we present a rare case of cutaneous metastasis of high-frequency microsatellite instability (MSI-high)/BRAFV600E-mutant cecum cancer. Case presentation A 77-year-old woman presented at the outpatient clinic with a subcutaneous mass on her left back. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Although a few cases of cutaneous metastasis of BRAF-mutant CRC have been reported in fact, the number is small, and further accumulation of cases is needed to explore the relationship between BRAF mutation and cutaneous metastasis [12,20,41]. Yunoki et al reported the first case of cutaneous metastasis of CRC that was MSI-H and BRAF V600E-mutant [42]. In that case, liver and lung metastases were observed simultaneously with the diagnosis of cutaneous metastasis of cecum cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few cases of cutaneous metastasis of BRAF-mutant CRC have been reported in fact, the number is small, and further accumulation of cases is needed to explore the relationship between BRAF mutation and cutaneous metastasis [12,20,41]. Yunoki et al reported the first case of cutaneous metastasis of CRC that was MSI-H and BRAF V600E-mutant [42]. In that case, liver and lung metastases were observed simultaneously with the diagnosis of cutaneous metastasis of cecum cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Clínicamente las metástasis deben ser distinguidas de los quistes simples, lipomas, neurofibromas o lesiones infecciosas 6 . En el cáncer de colon, la localización de la metástasis más frecuente es en la cicatriz abdominal de la cirugía (no es exclusivo de la cicatriz por incisión quirúrgica, sino también de cicatrices abdominales preexistentes), otros sitios de acuerdo a su incidencia son: la pelvis, espalda, tórax, extremidades, cara, párpados, fosas nasales, cuero cabelludo y hallux 2,5,6 .…”
Section: Caso Clínico Discusiónunclassified
“…Clínicamente las metástasis deben ser distinguidas de los quistes simples, lipomas, neurofibromas o lesiones infecciosas 6 . En el cáncer de colon, la localización de la metástasis más frecuente es en la cicatriz abdominal de la cirugía (no es exclusivo de la cicatriz por incisión quirúrgica, sino también de cicatrices abdominales preexistentes), otros sitios de acuerdo a su incidencia son: la pelvis, espalda, tórax, extremidades, cara, párpados, fosas nasales, cuero cabelludo y hallux 2,5,6 . Puede asumir una variedad de apariencias morfológicas, entre ellas, nódulos de color violáceo firmes, móviles, indoloros, únicos o múltiples y en algunos casos simular quistes epidérmicos, neurofibromas, lipomas e incluso en forma de eritema 1,5 .…”
Section: Caso Clínico Discusiónunclassified
See 1 more Smart Citation